1997
DOI: 10.1037/0278-6133.16.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Health locus of control and value for health in smokers and nonsmokers.

Abstract: A representative sample of 11,401 persons completed a questionnaire, including measures of health locus of control, value for health, and smoking frequency. Smokers held stronger internal, chance, and powerful others beliefs than never smokers. Ex-smokers had lower scores on internal and chance dimensions and placed a higher value on their health than smokers. The interaction between chance health locus of control and value for health was a significant predictor of smoking status, suggesting that health value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 19 publications
(22 reference statements)
6
39
1
2
Order By: Relevance
“…Earlier studies indicated that health locus of control was a significant predictor to alcohol abuse. 26,27 The findings of the present study also support the above views.…”
Section: Alcohol and Other Drug Abusesupporting
confidence: 81%
See 2 more Smart Citations
“…Earlier studies indicated that health locus of control was a significant predictor to alcohol abuse. 26,27 The findings of the present study also support the above views.…”
Section: Alcohol and Other Drug Abusesupporting
confidence: 81%
“…Similar studies that have examined the interaction effect between health behavior and health locus of control have generally produced positive results. 22,26 use' and 'alcohol and other drug use' were found to be better when compared to the other dimensions of positive Health Behavior. 19 In this context, it is to be noted from Granner's 20 comments that, fruit and vegetable availability was the most consistent associate of intake of adolescents.…”
Section: Protective Behaviormentioning
confidence: 96%
See 1 more Smart Citation
“…PHLC and/or CHLC are classified as "external" belief, and IHLC as "internal" belief (Wallston and Wallston 1978). In Western countries, the relationships between MHLC score and socio-demographics and various types of health-related behavior such as smoking, drinking, or exercise have been investigated (Slenker et al 1985;Calnan 1989;Fleming and Barry 1991;Schank and Lawrence 1993;Stuart et al 1994;Bennett et al 1997;Paxton and Sculthorpe 1999). Most of the previous studies agreed that people with low socioeconomic status (low income, fewer years of education) or adverse health-related behavior (such as smoking or excess drinking) tend to have higher "external" scores, while people with high socioeconomic status or beneficial health behavior such as regular exercise tend to have higher "internal" scores.…”
mentioning
confidence: 99%
“…Um exemplo disso são os trabalhos sobre a relação entre locus de controle saudável e a execução das condutas relacionadas com a saú-de (Benett, Moore, Norman, Murphy & Tudor, 1997). Parte destas investigações tem refletido uma relação positiva entre as pontuações da dimensão interna e as condutas promotoras de saúde e/ou uma relação negativa entre as pontuações da dimensão sorte e as condutas saudáveis ou positivas.…”
Section: Locus De Controleunclassified